Perceptions de l’aspect en français — des aperçues sémantiques et syntaxiques - Pozierak-Trybisz, Izabela (Neophilologica, 2017)
The article deals with the contrasting semantic analysis of the corpus of French and Polish examples whose inherent aspect is identical, but the so-called contextual aspect is defined differently. Aspect is now considered as a semantic category, an inherent proportion of the meaning of each predicate. However, there are differences in the typology of aspect categories, among others in French and Polish. Differences in the classification of contextual aspect belong to different methodologies, especially in the different ways of approaching semantic analyses. The aim of the article is to prove that the two ways of seeing meaning influence the view that one can have of the inherent and contextual aspect, and also to put some order in the existing classifications. The applied methodology is semantic-based grammar in the line of the Polish School of Semantics.